Serum procalcitonin has no significance in the diagnosis of periprosthesis joint infection before total hip and knee replacement - Sun, Xiaobo; Zhang, Haitao; Liu, Yuting; Lai, ZhiWei; Zeng, Yirong (Frontiers in Surgery, 2023)
Background Currently, there is no “gold standard” for early diagnosing PJI. The diagnosis of periprosthetic joint infection (PJI) is a challenging problem in the clinic. As we know, many serum markers have been used in the early diagnosis of PJI. The aim of this study was to validate the value of PCT in the diagnosis of PJI. Methods A retrospective review of 77 patients with revision arthroplasties from January 2013 to July 2020 was conducted. PJI was defined using the modified Musculoskeletal Infection Society (MSIS) criteria combined with follow-up results. Besides medical history, clinical and laboratory data was gathered. Preoperative blood was taken for serum PCT and other biomarkers measurement. Receiver operating characteristic (ROC) curves were generated to evaluate the biomarkers’ diagnostic performance and optimal cut-off value. Results Forty-one patients were identified as the PJI group (27 hips and 14 knees), while thirty-six patients were identified as the aseptic loosening (AL) group (33 hips and 3 knees). The AUCs for C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), Platelets (PLT), Fibrinogen (FIB), and Procalcitonin (PCT) were 0.845 (95% CI 0.755–0.936, p < 0.001), 0.817 (95% CI 0.718–0.916, p < 0.001), 0.728 (95% CI 0.613–0.843, p < 0.001), 0.810 (95% CI 0.710–0.910, p < 0.001) and 0.504 (95% CI 0.373–0.635, p = 0.950), respectively. Higher Area under the Curve (AUC) values were obtained for the combinations of PCT and CRP (AUC = 0.870) (95% CI, 0.774–0.936), PCT and ESR (AUC = 0.817) (95% CI, 0.712–0.896), PCT and PLT (AUC = 0.731) (95% CI, 0.617–0.825), PCT and FIB (AUC = 0.815) (95% CI, 0.710–0.894). The serum PCT indicated a sensitivity of 19.51% and a specificity of 83.33% for diagnosing PJI. When the optimal cut-off value for PCT was set as 0.05 ng/ml, its positive and negative likelihood ratios were 57.1% and 47.6%, respectively. Conclusion In conclusion, serum PCT appeared to be no reliable biomarker in differentiating PJI from aseptic loosening before revision arthroplasties. However, PCT combined with other biomarkers further increases the diagnostic accuracy.